PENGUATAN KAPASITAS KELEMBAGAAN PEMERINTAH DAERAH SEBAGAI AGENDA UTAMA OPTIMASI PENGELOLAAN DAERAH PERBATASAN - Haris Faozan (Pusjar SKPP Lembaga Administrasi Negara, 2006)
Matters related with regional borders have become part of the core issues of Indonesian incumbent-government. The government efforts to deal with the developing issues haves continuously been made. There are at least two fundamental matters that have drawn the attention of government, i.e. physically determination of state borders and the management of territorial borders development. In relation to the latter, it is a right time for the government to not only studying but also initiating a specific government institution that will be in charge of managing the potencies and complexities of the territorial borders. At present it is deemed necessary for the central government to facilitate the establishment of such institution to promote the development of border areas. Therefore, this is an important agenda that should be carried out soon. Moreover, local governments along the border areas, in general, require support and facilitation from the central government in developing their region. Keywords: kapasitas kelembagaan, daerah perbatasan.